(untitled) (Journal of Engineering, 2010)
The aim of sustainability represents one of the most important aims that most architects sought for achieving it. Thus, the economical factor appears to have the priority within the set of factors leading to this aim, where the effect of this factor appears much clearly in housing projects in comparison to other types of buildings. Therefore, many attempts and experiments were adopted in the field of economical low cost housing in different places of world. These attempts were associated with many aspects concerning the subject of achieving the possible economy of house of all levels. In spite of the numerous attempts that were adopted on the local level for putting general lines for the economical housing directions; the results were not in the desired level especially if we look at the subject within the determiners of local environment and their hard climatic considerations. This research deals with the conditions of sustainable house within two pivots; the first is environmental that looks after the conditions of local environment and the second is constructive where it is related to determine the modes, devices and constructional material. The second pivot represents the considerations concerning the design regarding the methods and devices of construction. Thus, the two pivots together throughout their subdividing give important stages for achieving the aim of sustainability of house. The research depends on the analytical descriptive technique for several economical executive housing samples in different places of world and gives and evaluation of the possibility of getting benefit of them locally.